(untitled) (Global Journal of Human-Social Science, 2013)
Shrines of the Sufi saints are the signs of Peace Harmony Tolerance and sympathy Today s peoples have great faith on Sultans peers and come on the shrines for making woves Come on shrines and making woves have become an important part of the social life of the people Not only Muslims but also non-Muslims came on shrines and follow the teachings of the Sufis in every sphere of life Female came on shrines in great numbers than male because they have great belief on woves and follow the teachings of the predecessors peers blindly Fake peers are also found in great numbers and they deceive people through different ways It has become an important issue in our society and increasing with the passage of time On the other hand people have become materialistic and leave religious values They are accepting wrong beliefs values and teachings which presented by the fake religious leaders and predecessors of the Sufis shrines Therefore present research study was conducted in sociology Present study was conducted in district Jhang on the shrines of Sultan s Sufi Saints For this purpose five Sultan s Sufi Saints shrines were selected Sufi Saint s played a vital role in the preaching of Islam in Jhang People of Jhang were and are very rigid in their traditions and culture Sufi Saints preached Islam here with love and through miracles They were true representer of Islamic teachings and Holy Prophet PBUH teachings